Pengaruh Pendidikan Kewirusahaan, Mental Berwirausaha, Dan Lingkungan Keluarga Terhadap Minat Berwirausaha Pada Mahasiswa Prodi Manajemen Universitas Islam Malang - Azizah, Siti Nur; Salim, Muhammad Agus; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The study adopts a quantitative approach employing purposive sampling. Its objective is to ascertain whether entrepreneurship education, entrepreneurial mentality, and family environment impact the interest in entrepreneurship among students enrolled in the Management program at the Islamic University of Malang. Primary data is collected through the distribution of questionnaires. Quantitative analysis, regression analysis, and determination coefficient (  analysis are conducted using SPSS 23. The population comprises 474 students, with 90 students selected as respondents through the Slovin formula. Findings indicate that entrepreneurship education does not influence interest in entrepreneurship, whereas entrepreneurial mentality and family environment do. The determination coefficient test yields a result of 57.3%, indicating the proportion of variance in interest in entrepreneurship explained by entrepreneurship education, entrepreneurial mentality, and family environment, while 42.7% is attributed to other variables beyond the scope of this study. Keywords: Entrepreneurship Education, Entrepreneurial Mentality, Family Environment, Interest In Entrepreneurship.